RETRACTED: Expression of Concern: The Turnaway Study: A Case of Self-Correction in Science Upended by Political Motivation and Unvetted Findings - Coleman, Priscilla K. (Frontiers in Psychology, 2022)
This review begins with a detailed focus on the Turnaway Study, which addresses associations among early abortion, later abortion, and denial of an abortion relative to a range of outcomes including mental health indicators. The motivation for conducting the study, methodological deficiencies, and bias are specifically addressed. Despite serious departures from acceptable scientific practices, journals in psychology and medicine have published dozens of articles generated from Turnaway Study data. The high volume of one-sided publications has stifled dialogue on potential adverse psychological consequences of this common procedure. Following a critical analysis of the Turnaway Study, an overview of the strongest studies on abortion and mental health is provided. This comprehensive literature comprised of numerous large-scale studies from across the globe has been largely ignored by the scientific community and the public, as the Turnaway Study dominates the media, information provided to women, and legal challenges involving abortion restrictions. In the final section of this article, literature reviews by professional organizations are considered, demonstrating that the biased science characterizing the Turnaway Study is aligned with a pervasive and systemic phenomenon wherein deriving reliable and valid results via careful attention to methodology and scrutiny by the scientific community have been supplanted by politics.